2000
DOI: 10.1037/0022-006x.68.4.650
|View full text |Cite
|
Sign up to set email alerts
|

Reducing risk factors for eating disorders: Comparison of an Internet- and a classroom-delivered psychoeducational program.

Abstract: This controlled trial compared Internet- (Student Bodies [SB]) and classroom-delivered (Body Traps [BT]) psychoeducational interventions for the reduction of body dissatisfaction and disordered eating behaviors/attitudes with a control condition. Participants were 76 women at a private university who were randomly assigned to SB, BT, or a wait-list control (WLC) condition. Measures of body image and eating attitudes and behaviors were measured at baseline, posttreatment, and 4-month follow-up. At posttreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(140 citation statements)
references
References 27 publications
4
127
0
9
Order By: Relevance
“…Online websites and support groups provide information, support, acceptance and a sense of real-time understanding to patients and their families and friends, and can promote better informed patients who engage their physicians more, stimulated by information they have found online (Aspden & Katz, 2001;Celio et al, 2000;McKay et al, 2001;Paterniti et al, 1999;Rice, 2001Rice, , 2003Preece & Ghozati, 2001;Sharf, 1997;Till, 2003;Wellman, 1995;Wikgren, 2001;Williams et al, 2002;Winzelbert et al, 2003). Nine percent of health seekers in both the August 2002 (Fox & Rainie, 2002a) and the June 2001 survey (Fox & Rainie, 2002b) said they had ever participated in an online support group concerned about a particular health or medical issue, though, in the second survey, more frequent health seekers (several times a month or more) were more likely to have done so (13%).…”
Section: Online Health Information As a Source For Support And Interamentioning
confidence: 99%
“…Online websites and support groups provide information, support, acceptance and a sense of real-time understanding to patients and their families and friends, and can promote better informed patients who engage their physicians more, stimulated by information they have found online (Aspden & Katz, 2001;Celio et al, 2000;McKay et al, 2001;Paterniti et al, 1999;Rice, 2001Rice, , 2003Preece & Ghozati, 2001;Sharf, 1997;Till, 2003;Wellman, 1995;Wikgren, 2001;Williams et al, 2002;Winzelbert et al, 2003). Nine percent of health seekers in both the August 2002 (Fox & Rainie, 2002a) and the June 2001 survey (Fox & Rainie, 2002b) said they had ever participated in an online support group concerned about a particular health or medical issue, though, in the second survey, more frequent health seekers (several times a month or more) were more likely to have done so (13%).…”
Section: Online Health Information As a Source For Support And Interamentioning
confidence: 99%
“…Health promotion and education interventions have been successfully delivered online 17,18 , and there are early reports of psychological interventions via the internet 19 . A randomized controlled trial showed that an e-mail discussion group had a positive effect on health status in people with chronic back pain 20 .…”
Section: The Internet As a Tool For The Delivery Of Healthcarementioning
confidence: 99%
“…Recent meta-analyses have revealed design features of prevention programs that lead to larger effect sizes and one such feature is the use of validated outcome measures of targeted risk factors rather than programs evaluated without such measures (Stice & Shaw, 2004;Stice et al, 2007). The psychometric properties of measures of disordered eating attitudes and behaviours have often been evaluated in young-adult female populations given this demographic is commonly the target of both prevention (e.g., Celio et al, 2000;Winzelberg et al, 2000) and treatment efforts (e.g., Agras, Walsh, Fairburn, Wilson, & Kraemer, 2000;McIntosh et al, 2005). However, prevention programs delivered to younger and in particular, mixed-gender audiences often have far less psychometric data available on which to select valid and reliable outcome measures.…”
Section: Introductionmentioning
confidence: 99%